MELANGKAH TANPA PENUNTUN: MENGEKSPLORASI DAMPAK KEHILANGAN AYAH TERHADAP KESEHATAN MENTAL DAN EMOSIONAL ANAK-ANAK - Indra Abdul Majid; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The role and function of parents towards children are very important in the family. The absence of one person, especially the father, in guiding and supporting the development of the child will have a direct, unknown impact on a family, as it has a significant impact on the child's health and emotional well-being. Most children unconsciously have problems with the role of a lost father or fatherless in their lives; even Indonesia occupies the third place in the roles of a missing father or fatherless. The study explores the impact of father loss on the child's mental and emotional health, factors that cause fatherlessness, and adaptive strategies to cope with the difficulties that arise after the loss of a father. This research uses a library study method, or literature review, which involves collecting books, articles, and previous research that supports research with a qualitative approach. The results point to the fact that losing a father can have a significant impact on a child's mental and emotional health. This study provides insight into the importance of the father's role in the family and the importance of social support to cope with the impact fatherless.